Training in innovation and entrepreneurship: A Design Thinking teaching experience - Bedregal-Alpaca, Norka (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
A Design Thinking (DT) teaching experience developed in the context of compulsory remote education is reported. The training process was managed using ICT tools. We worked with 23 university students, the objective was to generate innovative and useful proposals in their context, proposals focused on the needs of potential users. To assess the experience, a questionnaire was applied to the students. The results show innovative proposals that helped them develop technological skills and transversal competences. It is concluded that students favorably perceive the didactic strategies implemented, which opened new alternatives for their personal and professional development.